Femtosecond Laser Inscribed Multiwavelength Cascaded FBG Array Using Point-By-Point Method for Temperature Sensing Based on Swept Laser Demodulation Technique - Jia Liu; Bai Zhang; Yiwei Liu (International Journal of Optics)
A femtosecond laser inscribed quintuple-wavelength cascaded fiber Bragg grating (FBG) array for temperature sensing system based on swept laser source was proposed and experimentally demonstrated. In the proposed system, five cascaded 2-mm length FBGs were inscribed using the point-by-point method with a grating spacing of 2 cm through fiber acrylate coating. In addition, the demodulator based on swept modulated grating Y-branch (MG-Y) laser source was constructed. In the experiment, the FBG array was hold on temperature platform for heating and cooling test during 30∼90°C range, and sensitivity was more than 8.9 pm/°C with a linearity of 0.989.